TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA ZAKAT BERBASIS WEBSITE PADA LEMBAGA PENGELOLA ZAKAT DI INDONESIA - Nina Karina Karim; Elin Erlina Sasanti; Indria Puspitasari Lenap; Nungki Kartikasari (Jurnal Riset Akuntansi, 2019)
This study aims to analyze the transparency and accountability of zakat fund management based on website of zakat institutions in Indonesia. The type of research employed was a descriptive research with content analysis method. By adopting a non probabilty sample with purposive sample technique. Population in this reasearch are all national zakat institutions which listed on Directorate General of Tax in the year of 2019. Based on thecriteria, we obtained 10 sample of zakat institutions. The research showed that none of these zakat institutions which have full disclosure of financial statement based on Accounting Standard no. 109 and amil governance by website and there was only Baznas had the highest level of disclosure. Whilst, by 9 of privat zakat institutions, there were 5 institutions have more than 60% disclosure and the rest (3 institutions) were under 50%. This finding indicates that publication level of financial and non financial information in zakat institutions by using the internet is low. The lack of website disclosure can caused by regulation factor which is not requires the zakat institutions to disclose their financial statement and amil governance performance by using internet.